DIVERSITY OF PLANKTON COMMUNITY AND WATER QUALITY IN LEKAN AARE LAKE, ABEOKUTA, NIGERIA - ODULATE, D.O; OLADOYE, A.O; OMONIYI, I.T.; EDUN, O. A; BUSARI, R. A; AJAGBE, S. O (Nigerian Journal of Fisheries, 2017)
Phytoplankton composition, temporal distribution and diversity with physico-chemical water parameters were studied based on monthly sampling from three locations in the lake. The lake was delineated into three sampling areas. Each location sited in each sampling area. The study was carried out for the period of twelve months. Of the four groups identified in this study (Chlorophyta (52%), Bacillariophyta (26%), Cyanophyta (20%) and Xantophyta (2%) consisting of 54 species. Xanthophyta was less diverse with one representative while Chlorophyta had the highest number of genera. Highest taxa (37) was recorded in June. Simpson diversity and evenness indices were generally high during the study period with highest values of 0.96 (June) and 0.95 (December) and least in August (0.85) and (0.70) respectively. High correlation coefficients 0.91 and 0.75 recorded in the relationship among TDS/EC and air/water temperature respectively. Canonical correspondence showed strong relationship between EC and TDS which were favourably dispose to abundance of Aphanocapsa, Nostoc and Scenedesmus with negative response of Melosira, Polycystis, Amphora, and Microspora. The monitoring of the lake system is essential for its sustainable management.